Approaching autonomy: post-socialist conceptualism in Chinese art - Li, Yu-Chieh (Modern Asian art and visual culture, 2025)
This book explores works by key artists who shaped conceptualism in post-Mao China. Drawing from understudied archival materials and qualitative research, it analyzes artistic struggles for autonomy, re-evaluating Robert Rauschenberg's 1985 exhibition in Beijing and Chinese artists' exploration of appropriation, affect, dehumanization, and collective practice since the 1980s. A continuous development can be found in the politics and aesthetics of post-socialism, which has struggled to define its space for expression, from the 1980s until today
Dissertation eingereicht unter dem Titel: Democratic Art in Post-Socialist China Appropriation, Dehumanization, and Audience Participation, 1985-95
Keywords: Hochschulschrift; Concept-art; China